Modern Cryptography: A Comprehensive Review of Symmetric and Asymmetric Encryption Algorithms - Maha A. Sayal (Review of Multidisciplinary Academic and Practice Studies, 2026)
Purpose: This study aims to provide a comprehensive comparative review of modern cryptographic algorithms, specifically examining symmetric encryption techniques (AES and RC4) and asymmetric encryption techniques Rivest Shamir Adleman (RSA), to evaluate their performance, structure, and suitability for contemporary digital security applications. Research Methodology: A systematic literature review methodology was employed to analyze and compare cryptographic primitives. Primary and secondary sources, including peer-reviewed journals and conference proceedings published predominantly within the last five years, were examined. Comparative parameters including key size, block size, structure, speed, security level, and computational cost were used to evaluate each algorithm. Results: The findings demonstrate that symmetric algorithms, particularly Advanced Encryption Standard (AES), exhibit superior speed and computational efficiency compared to asymmetric algorithms such as RSA. AES with a 128-bit block size and variable key lengths of 128, 192, or 256 bits offers excellent security through its substitution-permutation network. RC4, as a stream cipher, proves effective for real-time and resource-constrained environments. RSA, while computationally expensive, remains indispensable for secure key exchange and digital authentication. Conclusions: Modern cryptographic systems benefit from hybrid approaches integrating both symmetric and asymmetric algorithms to balance security and computational efficiency. AES remains the gold standard for symmetric encryption, while RSA continues to underpin public-key infrastructure. Limitations: This study is limited to three primary algorithms (AES, RC4, RSA) and does not encompass all emerging lightweight cryptographic protocols or post quantum cryptographic schemes. Contributions: This paper contributes a structured, comparative analysis of foundational cryptographic algorithms, bridging classical cryptographic theory with current implementation standards, providing researchers and practitioners with a consolidated reference framework.